Positive electrode active material for lithium ion secondary battery and method for producing same
By using the lithium nickel composite oxides with a specific crystal structure and covering the layer as a positive active substance, the problem of poor circulation characteristics of lithium ion secondary batteries under high voltage conditions has been solved, and higher capacity maintenance rates are achieved. Battery life.
Patent Information
- Application Number
- CN202380042238.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-23
- Filing Date
- 2023-05-23
- Publication Date
- 2025-01-28
AI Technical Summary
In the existing lithium-ion secondary batteries, after repeated charging and discharging with high voltage, the capacity of the positive electrode active substance is significantly reduced and the circulation characteristics are poor.
The lithium nickel -composite oxides with a specific crystal structure and overwriting are used as positive active substances, and the material is manufactured by hybrid processes, firing processes, and covering processes. The lithium nickel composite oxide particles of this material have an R-3M crystal structure, including li, Ni, Mn, and element m (such as CO or Al, etc.), and formation containing li and other elements on the surface of the particles.
The charging and discharge cycle characteristics of lithium ion secondary batteries are improved, the service life of the battery is extended, and a high capacity maintenance rate is maintained under high voltage conditions.
Smart Images

Figure CN119384732A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a positive electrode active material for a lithium ion secondary battery and a method for manufacturing the same. Background Art
[0002] In recent years, with the improvement of environmental awareness, the conversion from gasoline vehicles to hybrid vehicles and electric vehicles has been continuously promoted. In particular, there is a strong expectation for the development of a small and lightweight secondary battery with high energy, which is essential for the popularization of electric vehicles. As such a secondary battery, there is a lithium ion secondary battery.
[0003] Currently, ordinary lithium ion secondary batteries use lithium transition metal composite oxides such as LiCoO2, LiNiO2, and LiMn2O4 as positive electrode active materials, and use lithium metal, lithium alloy, metal oxide, carbon, etc. as negative electrode active materials.
[0004] In addition, when using a non-aqueous electrolyte as the electrolyte, for example, an electrolyte in which a Li salt such as LiClO4 or LiPF6 is dissolved in an organic solvent such as ethylene carbonate, dimethyl carbonate, or ethyl methyl carbonate is used as a supporting salt.
[0005] Such lithium ion secondary batteries are currently being actively studied and developed. Among them, lithium ion secondary batteries using layered or spinel-type lithium metal composite oxides as the positive electrode material can obtain a high voltage of 4V level, and thus are being promoted to practical use as batteries with high energy density.
[0006] As the materials mainly proposed so far, there can be mentioned lithium cobalt composite oxide (LiCoO2) which is relatively easy to synthesize, lithium metal composite oxide (LiNiO2) using nickel cheaper than cobalt, lithium nickel cobalt manganese composite oxide (LiNi 1 / 3Co 1 / 3 Mn 1 / 3 O2), lithium manganese composite oxide (LiMn2O4) using manganese, etc.
[0007] For example, Patent Document 1 describes a Li-Ni composite oxide particle powder, which is characterized by being Li x (Ni y Co 2(1-y) / 5 Mn 3(1-y) / 5 ) 1-z M z O2 (1.00 ≤ x ≤ 1.10, 0.65 < y < 0.82, 0 ≤ z ≤ 0.05, M is at least one element selected from Al, Zr, and Mg). In addition, the positive electrode containing the positive electrode active material composed of the Li-Ni composite oxide particle powder has a high initial discharge capacity and excellent initial charge-discharge efficiency.
[0008] Prior Art Documents
[0009] Patent Literature
[0010] Patent Document 1: International Publication No. 2014-061654 Summary of the invention
[0011] Problems to be solved by the invention
[0012] However, in order to realize the high energy density of lithium ion secondary batteries, it is preferred to charge and discharge the battery at a high voltage, and it is preferred to use a positive electrode active material with a high average operating voltage. Examples of such positive electrode active materials include LiNi 0.33 Co 0.33 Mn 0.33 O2、LiNi 0.6 Co 0.2 Mn 0.2 O2 or the like is a positive electrode active material containing Mn and having a Ni ratio of 30% or more.
[0013] Therefore, the inventors have studied the application possibility of lithium ion secondary batteries for the positive active materials as mentioned above. As a result, the inventors have found that for the above-mentioned positive active materials in the past, when repeatedly charging and discharging at high voltage, there is a problem that the capacity after repeated charge and discharge cycles is significantly reduced compared with the capacity (initial capacity) before repeated charge and discharge cycles.
[0014] For example, Patent Document 1 mentions the initial discharge capacity and the initial charge and discharge efficiency of the positive electrode active material, but does not mention the cycle characteristics under high voltage at all.
[0015] The present invention has been made in view of the above-mentioned problems, and an object of the present invention is to provide a positive electrode active material having improved charge-discharge cycle characteristics as a positive electrode active material for a lithium ion secondary battery.
[0016] Means for solving problems
[0017] In a first aspect of the present invention, there is provided a positive electrode active material for a lithium ion secondary battery, which has particles of a lithium nickel composite oxide and a coating layer covering the particle surface. The particles of the lithium nickel composite oxide have a crystal structure belonging to the space group R-3m and contain at least Li, Ni, Mn, and element M. The molar ratio of each element is represented by Li:Ni:Mn:M:Nb = a:(1-x-y):x:y:z (0.95 ≤ a ≤ 1.10, 0 < x ≤ 0.5, 0 < y ≤ 0.5, 0 < z < 0.05, 0 < x + y + z ≤ 0.7, element M is Co, or element M is Co and at least one selected from the group consisting of Al, Zr, Si, Zn, Nb, and Ti). The Li site occupancy rate is 92% or more and 98% or less. In the cumulative volume distribution curve of the particle size distribution, the particle diameter (D50) corresponding to a cumulative volume rate of 50% is 8 μm or less. The crystallite diameter calculated by the Scherrer method from the diffraction peak attributed to the (003) plane measured by XRD is 70 nm or more and 140 nm or less. The amount of eluted lithium ions determined by neutralization titration is 0.20 mass% or more and 1.00 mass% or less relative to the total amount of the particles of the lithium nickel composite oxide. The coating layer is a composite oxide containing Li and at least one element selected from the group consisting of Al, Si, Ti, V, Ga, Ge, Zr, Nb, Mo, Ta, and W.
[0018] In addition, the particles of the lithium nickel composite oxide contain secondary particles formed by aggregation of a plurality of primary particles, and have a porous structure having a plurality of void portions where no primary particles exist in the secondary particles. The specific surface area measured by the nitrogen adsorption BET method is preferably 0.3 m 2 / g or more and 2.0 m 2 / g or less. In addition, it is preferable that at least a part of the niobium contained in the particles of the lithium nickel composite oxide segregates at the interface of the primary particles. In addition, the average thickness of the coating layer is preferably 1 nm or more and 15 nm or less.
[0019] In a second aspect of the present invention, there is provided a method for manufacturing the above positive electrode active material for a lithium ion secondary battery, which includes: a mixing step of mixing a nickel composite compound, a niobium compound, and a lithium compound to obtain a mixture; a firing step of firing the mixture to obtain particles of a lithium nickel composite oxide; and a coating step of causing a coating liquid containing at least one element selected from the group consisting of Al, Si, Ti, V, Ga, Ge, Zr, Nb, Mo, Ta, and W to adhere to the surface of the particles of the lithium nickel composite oxide to form a coating layer.
[0020] In addition, the nickel composite compound includes a nickel composite oxide, and preferably includes an oxidation roasting step of oxidizing and roasting the nickel composite hydroxide adjusted by the crystallization reaction to obtain the nickel composite oxide. In addition, it is preferred that after the coating step, there is a heat treatment step of heat treating the particles of the lithium nickel composite oxide having the coating layer formed on the surface at 300°C or above.
[0021] Effects of the Invention
[0022] The positive electrode active material of the present invention improves the charge-discharge cycle characteristics when used as a positive electrode active material for a lithium ion secondary battery. In addition, the production method of the present invention can produce the positive electrode active material with high productivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 It is a schematic diagram showing an example of the positive electrode active material according to the present embodiment.
[0024] Figure 2 This is a diagram showing an example of a method for producing a positive electrode active material according to this embodiment.
[0025] Figure 3 This is a diagram showing an example of a method for producing a nickel composite compound according to the present embodiment.
[0026] Figure 4 This is an explanatory diagram of the cross-sectional structure of a coin-shaped battery for evaluation used in battery evaluation.
[0027] Figure 5 This is an explanatory diagram of a laminated battery for evaluation used in battery evaluation. DETAILED DESCRIPTION
[0028] Hereinafter, an embodiment of the present invention will be described with reference to the accompanying drawings. It should be noted that in the accompanying drawings, in order to facilitate the understanding of each structure, a part is emphasized or a part is simplified for representation, and sometimes the actual structure or shape, scale, etc. are different. In addition, the present invention is not limited to the following embodiments, and various deformations and substitutions can be made to the following embodiments without departing from the scope of the present invention.
[0029] 1. Positive electrode active material for lithium-ion secondary batteries
[0030] First, a configuration example of a positive electrode active material for a lithium ion secondary battery (hereinafter also simply referred to as a “positive electrode active material”) according to the present embodiment will be described.
[0031] Figure 1 Schematically shows an example of a positive electrode active material according to this embodiment. Figure 1As shown, the positive electrode active material 10 has particles 1 of a lithium nickel composite oxide and a coating layer 2 covering the surface of the particles 1. Hereinafter, each component will be described.
[0032] (1) Particles of Lithium Nickel Composite Oxide
[0033] The particles 1 of the lithium nickel composite oxide have a crystal structure belonging to the space group R-3m and are a composite oxide containing at least lithium (Li), nickel (Ni), manganese (Mn), element M, and niobium (Nb).
[0034] (Composition)
[0035] When the molar ratio of the amounts of substances of the respective elements contained in the particles 1 of the lithium nickel composite oxide is represented by Li:Ni:Mn:M:Nb = a:(1 - x - y - z):x:y:z, 0.95 ≤ a ≤ 1.10, 0 < x ≤ 0.5, 0 < y ≤ 0.5, 0 < z < 0.05, and 0 < x + y + z ≤ 0.7 are satisfied. Additionally, in the above molar ratio, it is preferably satisfied that 0.97 ≤ a ≤ 1.08, 0 < x ≤ 0.3, 0 < y ≤ 0.3, 0 < z ≤ 0.02, and 0 < x + y + z ≤ 0.5.
[0036] In the above molar ratio, a representing the content ratio of Li is 0.95 ≤ a ≤ 1.10, and it can also be 0.97 ≤ a ≤ 1.08. When a is less than 0.97, Li is lacking in the positive electrode active material, which easily leads to a reduction in the capacity as a battery material. When a is greater than 1.10, the crystal structure of the particles 1 of the lithium nickel composite oxide grows excessively, the primary particles become coarser, and cracks in the particles 1 are likely to occur, thus easily impairing the durability. Additionally, a can be 1.00 or more, and it can also be greater than 1.00.
[0037] In the above molar ratio, (1 - x - y - z) representing the content ratio of Ni is 0.3 or more and less than 1.0, preferably 0.5 or more and less than 1.0. Additionally, the lower limit range of the content ratio of Ni is preferably 0.6 or more, and it can also be 0.7 or more. The higher the content ratio of (1 - x - y - z), the lower the voltage required for charging, and as a result, the higher the battery capacity. On the other hand, when (1 - x - y - z) is less than 0.3, the battery capacity becomes low.
[0038] In the above molar ratios, x representing the content ratio of Mn is 0 < x ≤ 0.5, which can be 0 < x ≤ 0.4 or less, or can be 0 < x ≤ 0.3 or less. When the content ratio of Mn is in the above range, high battery capacity and high thermal stability can be achieved. In addition, the lower limit of x representing the content ratio of Mn can be, for example, 0.05 or more.
[0039] In the above molar ratios, element M is preferably at least one selected from the group consisting of Co, Al, Zr, Si, Zn, and Ti. In addition, element M preferably contains at least one element selected from cobalt (Co) and aluminum (Al), can contain cobalt (Co) and aluminum (Al), and particularly preferably contains cobalt (Co). Element M is, for example, Co, or Co and at least one selected from the group consisting of Al, Zr, Si, Zn, and Ti. It should be noted that element M can be appropriately selected according to the use and required performance of the secondary battery composed of the positive electrode active material 10.
[0040] In the above molar ratios, y representing the content ratio of element M is 0 < y ≤ 0.5, preferably 0 < y ≤ 0.3, and can also be 0 < y ≤ 0.2. For example, when element M contains Co and Co is contained in the above range, high battery capacity and more excellent cycle characteristics are achieved. In addition, when element M contains Co, the range of Co (y1) can be, for example, 0 < y1 ≤ 0.3, or can be 0 < y1 ≤ 0.2. In addition, when element M contains Al, the range of Al (y2) can be, for example, 0 < y2 ≤ 0.1, or can be 0 < y2 ≤ 0.07.
[0041] In the above molar ratios, z representing the content ratio of Nb is 0 < z < 0.05, preferably 0 < z ≤ 0.02. When z is in the above range, high battery capacity can be achieved. When z is greater than 0.05, LiNb3O8 with low activity is sometimes generated, resulting in a decrease in battery capacity. In addition, for example, when z is in the range of 0.001 ≤ z ≤ 0.01, higher battery capacity can be achieved. In addition, z can be in the range of 0.002 or more and 0.006 or less.
[0042] In addition, the niobium contained in the particles 1 of the lithium nickel composite oxide may be dissolved in the interior of the primary particles or may be present at the interface of the primary particles. At least a portion of the niobium is preferably segregated at the interface of the primary particles. The details of the reason are not clear, but it can be imagined that, for example, by segregating niobium at the interface of the primary particles, in the positive electrode of the secondary battery having a non-aqueous electrolyte, the movement of Li ions in the secondary particles is reduced, thereby increasing the battery capacity. In addition, it is believed that by segregating at least a portion of the niobium at the interface of the primary particles, it is easy to adjust the amount of dissolved lithium described later to a specific range. It should be noted that the segregation of niobium can be confirmed, for example, by performing surface analysis / line analysis on the composition of the primary particle cross section using energy dispersive X-ray spectroscopy (STEM-EDX) using a scanning transmission electron microscope, and detecting niobium concentration at the grain boundaries between the primary particles.
[0043] (Crystal Structure)
[0044] The lithium nickel composite oxide particle 1 has a crystal structure belonging to the space group R-3m. When the lithium nickel composite oxide particle 1 has a crystal structure belonging to the space group R-3m, an increase in internal resistance can be suppressed in the secondary battery.
[0045] The crystal structure of the particle 1 of the lithium nickel composite oxide can be confirmed by powder X-ray diffraction (XRD) measurement. That is, it is preferred to detect the peak of the layered rock salt type crystal structure (the crystal structure belonging to the space group R-3m) belonging to the "R-3m" structure from the diffraction pattern obtained when the powder X-ray diffraction (XRD) measurement of the particle 1 of the lithium nickel composite oxide is performed. In particular, it is more preferred to detect only the peak of the layered rock salt type crystal structure belonging to the "R-3m" structure from the above diffraction pattern.
[0046] It should be noted that the lithium nickel composite oxide particle 1 may be a single phase of a lithium nickel composite oxide having a crystal structure of an "R-3m" structure, or may not be a single phase. In the case where it is not a single phase but is mixed with other compounds (such as impurities), it is preferred that the intensity of the heterogeneous peaks other than the layered rock salt structure of the "R-3m" structure does not exceed the peak intensity of the layered rock salt structure belonging to the "R-3m" structure.
[0047] (Li site occupancy)
[0048] The Li site occupancy of the positive electrode active material is 90% or more and 98% or less, and may be 92% or more and 98% or less, or 93% or more and 98% or less. The Li site occupancy represents the proportion of lithium (Li) of the lithium metal composite oxide in the lithium layer (Li site) of the layered structure. When the lithium site occupancy of the positive electrode active material is within the above range, it is believed that a cation mixing occurs in the positive electrode active material in which metals other than lithium move to the lithium ion site. When charging and discharging at a high voltage, it is believed that the positive electrode active material in which a cation mixing occurs at a specific ratio has a high charge and discharge capacity, while the expansion and contraction of the volume is suppressed, and the cycle capacity retention rate (durability) is improved.
[0049] The lower limit of the Li site occupancy may be 90% or more, 92% or more, 93% or more, or 95% or more. The upper limit of the Li site occupancy may be 98% or less.
[0050] It should be noted that the evaluation method of the Li site occupancy is not particularly limited, for example, it can be obtained by performing a full spectrum fitting analysis (Rietveld analysis) on the diffraction pattern obtained by using the X-ray diffraction method (XRD). As an X-ray diffraction device (XRD), for example, X'PertPRO (Spectris Co., Ltd.) can be used. In addition, for the diffraction pattern obtained by measuring the positive electrode active material, for example, in addition to the commonly widely used RIETAN-FP, analysis programs such as High_Score_Plus (Spectris Co., Ltd.) and JADE_PRO (Materials_Data Co., Ltd.) can be used for full spectrum fitting analysis to obtain the Li site occupancy.
[0051] (Crystallite diameter)
[0052] The crystallite diameter of the particle 1 of the lithium nickel composite oxide is preferably less than 140nm, more preferably more than 70nm and less than 140nm. In addition, the range including the upper limit of the crystallite diameter can be less than 130nm. It should be noted that the crystallite diameter can be calculated by the Scherrer method using the peak belonging to (003) of the above-mentioned XRD diffraction pattern. In the case where the crystallite diameter of the particle 1 of the lithium nickel composite oxide is greater than 140nm, sometimes the solid diffusion distance in the crystal becomes longer and the battery capacity is reduced. In addition, in the case where the crystallite diameter of the particle 1 of the lithium nickel composite oxide is less than 70nm, the crystal structure becomes unstable and the battery capacity is easily reduced. In addition, the lower limit of the crystallite diameter can be more than 70nm, can be more than 90nm, or can be more than 100nm. In addition, the upper limit of the crystallite diameter can be less than 140nm, can be less than 130nm, or can be less than 120nm.
[0053] (Amount of dissolved lithium ions)
[0054] Regarding the particles 1 of the lithium nickel composite oxide, the amount of eluted lithium ions obtained by neutralization titration is 0.20 mass % or more and 1.00 mass % or less relative to the total amount of the particles 1, preferably 0.25 mass % or more and 1.00 mass % or less, and may also be 0.30 mass % or more and 0.70 mass % or less. It should be noted that, regarding the amount of eluted lithium ions, the amount of lithium ions eluted into water when the particles 1 of the lithium nickel composite oxide are dispersed in water can be obtained by neutralization titration using hydrochloric acid. As a neutralization titration method, the Warder method and the Winkler method can be used.
[0055] When the amount of eluted lithium ions in the lithium nickel composite oxide particles 1 is less than 0.20 mass %, the battery capacity may decrease.
[0056] It should be noted that, when the particles 1 of the lithium nickel composite oxide contain niobium, the amount of dissolved lithium ions increases compared to the lithium nickel composite oxide that does not contain niobium. Therefore, for example, by using the manufacturing method described later, the niobium content is adjusted to the above range, and the amount of dissolved lithium is adjusted to 0.2% by mass or more, a positive electrode active material with a high discharge capacity can be obtained. However, in the case where the amount of dissolved lithium ions in the particles 1 of the lithium nickel composite oxide is greater than 1.00% by mass, the discharge capacity is reduced. In addition, the upper limit of the amount of dissolved lithium ions can be less than 1.00% by mass, can be less than 0.70% by mass, and can be less than 0.60% by mass. In addition, the lower limit of the amount of dissolved lithium ions can be more than 0.3% by mass, and can also be more than 0.4% by mass.
[0057] (Crystalline diameter and amount of dissolved lithium ions)
[0058] Furthermore, the lithium nickel composite oxide particles 1 preferably have a crystallite diameter of 140 nm or less and an amount of eluted lithium ions of 0.20 mass % or more.
[0059] That is, even if the crystallite diameter of the lithium nickel composite oxide particle 1 is 140 nm or less, when the amount of eluted lithium ions is less than 0.20 mass %, the battery capacity may decrease. The reason for this is not clear in detail, but it is speculated as follows.
[0060] The particles 1 of lithium nickel composite oxide include secondary particles formed by the aggregation of multiple primary particles. It is believed that the crystallite size of the particles 1 of lithium nickel composite oxide is positively correlated with the size of the primary particles constituting the secondary particles. The smaller the crystallite size, the more it exists at the particle interface between the primary particles. In addition, the dissolved lithium ions mainly exist at the particle interface between the primary particles. Therefore, in the case where the crystallite diameter is small and there are a large number of interfaces of primary particles, if the dissolved lithium ions present at the interface (surface) of the primary particles are excessively reduced, voids will be formed at the interface of the primary particles. In the case where there are a large number of voids at the interface of the primary particles, the positive electrode active material becomes easy to break during the electrode manufacturing process of the secondary battery, and the contact interface between the particles of the lithium nickel composite oxide and the electrolyte increases. In addition, it is believed that due to the side reactions occurring at the increased contact interface, the generated phase hinders the charge transfer between the electrolyte and the positive electrode active material, so the resistance of the battery becomes higher and the battery capacity decreases.
[0061] On the other hand, when the crystallite diameter of the particle 1 of the lithium nickel composite oxide is greater than 140nm, even if the amount of dissolved lithium ions is more than 0.20% by mass, the battery capacity will be reduced, so it is not preferred. It is believed that this is because the grain boundaries between the primary particles are reduced due to the coarsening of the primary particles, so the dissolved lithium ions become dispersed in blocks on the surface of the secondary particles, and the existence of the dissolved lithium ions itself becomes a resistance phase. It should be noted that the crystallite diameter and the amount of dissolved lithium can be adjusted to the above range, for example, by using the manufacturing method of the positive electrode active material described later. Furthermore, the particle 1 of the lithium nickel composite oxide is set to the above range by setting the crystallite diameter and the amount of dissolved lithium to the above range, and setting the Li site occupancy to a specific range, so that when charging and discharging at a high voltage, it is possible to take into account both the battery capacity and the charge and discharge cycle capacity maintenance rate at a high level.
[0062] (Particle structure)
[0063] The lithium nickel composite oxide particle 1 includes secondary particles formed by agglomeration of a plurality of primary particles. The lithium nickel composite oxide particle 1 may include primary particles alone or may be a mixture of primary particles alone and secondary particles.
[0064] When observed using a scanning electron microscope (SEM), a transmission electron microscope (TEM), etc., the average particle size of the secondary particles is preferably less than 8.0 μm, more preferably more than 3.0 μm and less than 8.0 μm. In addition, the secondary particles are preferably formed by a large amount of agglomeration of primary particles having a particle size of more than 0.1 μm and less than 2.0 μm. In addition, in the case of comprising a single primary particle, the primary particle preferably has a particle size of more than 1.0 μm and less than 8.0 μm. It should be noted that the average particle size of each particle can be obtained, for example, by calculating the average of the area equivalent circle diameters of more than 20 particles.
[0065] (Average particle size D50)
[0066] The particle size (D50, hereinafter also referred to as "average particle size D50") of the lithium nickel composite oxide particles 1 in the cumulative volume distribution curve of the particle size distribution is preferably 8 μm or less, more preferably 2 μm or more and 8 μm or less, more preferably 2 μm or more and 7 μm or less, and further preferably 3 μm or more and 7 μm or less. It should be noted that the average particle size (D50) refers to the particle size (D50) in the cumulative volume distribution curve of the particle size distribution measured by a laser diffraction scattering particle size analyzer when the cumulative volume rate is 50%.
[0067] When the average particle size D50 of the lithium nickel composite oxide particles 1 is 8 μm or less, the secondary battery using the positive electrode active material 10 for the positive electrode can improve the capacity retention rate after the cycle measurement at high voltage, and can obtain excellent battery characteristics such as thermal stability and high output power. It should be noted that when the average particle size D50 is 2 μm or less, it is easy to aggregate when the coating layer 2 is applied.
[0068] (Span of particle size distribution)
[0069] The index [(d90-d10) / volume average particle size Mv] representing the span of the particle size distribution of the lithium nickel composite oxide particle 1 is not particularly limited, and from the viewpoint of making the particle size uniform, it can be less than 0.7, less than 0.6, or less than 0.55. When the particle size is relatively uniform, it is easy to uniformly coat the coating layer 2 on the surface of the lithium nickel composite oxide particle 1, and good output characteristics can be obtained in the secondary battery. It should be noted that the lower limit of [(d90-d10) / volume average particle size Mv] is not particularly limited, for example, it is greater than 0.3. In addition, from the viewpoint of filling property, [(d90-d10) / volume average particle size Mv] can be greater than 0.7, and by using the method for manufacturing the positive electrode active material described later, the coating layer 2 can be relatively uniformly coated.
[0070] It should be noted that d10 refers to the particle size when the number of particles of each particle size is accumulated from the side with a smaller particle size, and its cumulative volume becomes 10% of the total volume of all particles, and d90 also refers to the particle size when the cumulative number of particles is accumulated, and its cumulative volume becomes 90% of the total volume of all particles. In addition, d10, d90 and volume average particle size Mv can be obtained by the volume cumulative value obtained by measuring using a laser diffraction scattering particle size analyzer in the same way as the average particle size D50.
[0071] (Specific surface area)
[0072] The specific surface area of the lithium nickel composite oxide particles 1 is not particularly limited, and may be, for example, 0.3 m 2 / g or more and 2.0m 2 / g or less, and can also be 0.3m 2 / g or more and 1.0m 2 / g or less. When the specific surface area is within the above range, the output characteristics are good. It should be noted that the specific surface area can be measured by the nitrogen adsorption BET method. In addition, the lower limit of the specific surface area can be 0.35m 2 / g or more, and can also be 0.40m 2 / g or above.
[0073] (2) Coating layer
[0074] The positive electrode active material 10 has a coating layer 2 on the surface of the lithium nickel composite oxide particle 1. By having the coating layer 2 on the surface of the particle 1, in a secondary battery having a positive electrode including the positive electrode active material 10, the lithium nickel composite oxide particle 1 can be prevented from directly contacting the electrolyte, thereby suppressing the surface degradation of the lithium nickel composite oxide particle 1.
[0075] The coating layer 2 is a composite oxide containing lithium (Li) and one or more elements selected from the group consisting of Al, Si, Ti, V, Ga, Ge, Zr, Nb, Mo, Ta and W. It should be noted that the constituent elements of the coating layer 2 other than lithium (Li) and oxygen (O) may be one or more. The coating layer 2 may be, for example, a composite oxide consisting of Li and Ti, or a composite oxide consisting of Li and Nb.
[0076] (Contents of the elements in the coating layer)
[0077] The coating amount of the coating layer 2 is not particularly limited and can be determined based on the specific surface area (m 2 / g) to adjust the coating amount. For example, per 1m 2 The coating layer 2 contains the constituent elements of the coating layer 2 (excluding Li and O) in a ratio of preferably 30 μmol to 600 μmol, more preferably 50 μmol to 400 μmol, based on the surface area.
[0078] In the case of lithium nickel composite oxide particles 1m 2 When the content of the constituent elements (excluding Li and O) of the coating layer 2 per surface area is 30 μmol or more, the coating layer 2 can be uniformly arranged on the entire surface of the lithium nickel composite oxide particle 1 .
[0079] In addition, the internal resistance of the secondary battery may be increased by providing the coating layer. 2 When the content of the constituent elements (excluding Li and O) of the coating layer 2 per surface area is 600 μmol or less, the coating layer 2 can be prevented from becoming an obstacle to the insertion / extraction reaction of lithium into the lithium nickel composite oxide particles 1, thereby reducing the internal resistance.
[0080] In the coating layer 2, the method for evaluating and calculating the content of the constituent elements (excluding Li and O) of the coating layer 2 is not particularly limited, and can be determined, for example, as follows.
[0081] First, the content of the constituent elements (excluding Li and O) of the coating layer 2 in 1 g of the positive electrode active material is measured by chemical analysis or the like. As a method of chemical analysis, measurement is performed by ICP (Inductively Coupled Plasma) emission spectroscopy or the like.
[0082] On the other hand, the specific surface area of the lithium nickel composite oxide particle 1 before being coated with the coating layer 2 is measured by the nitrogen adsorption BET method or the like.
[0083] Next, the content of the constituent elements (excluding Li and O) of the coating layer 2 in 1 g of the positive electrode active material is divided by the specific surface area (m 2 / g), the mass per 1m2 of the lithium nickel composite oxide particle 1 can be calculated. 2 Content of constituent elements (excluding Li and O) of the coating layer 2 per surface area.
[0084] It should be noted that, when the particles 1 of the lithium nickel composite oxide contain the constituent elements of the coating layer 2 (excluding Li and O), the difference in the content of the constituent elements (excluding Li and O) of the coating layer 2 before and after coating can be used as the content of the constituent elements (excluding Li and O) of the coating layer 2 used for coating.
[0085] (Average thickness of coating layer)
[0086] The average thickness of the coating layer is, for example, preferably from 2 nm to 20 nm, more preferably from 2 nm to 15 nm, and even more preferably from 5 nm to 15 nm.
[0087] It should be noted that the average thickness of the coating layer 2 can be calculated as follows: by observing with a scanning electron microscope (SEM), a transmission electron microscope (TEM), etc., or analyzing with a spectrometer such as an energy dispersive X-ray spectrometer (EDS) or an electron energy loss spectroscopy (EELS) attached thereto, the layer uniformly formed on the surface of the particles 1 of the lithium nickel composite oxide is measured and calculated. It should be noted that, in the case where the thickness of the coating layer 2 varies depending on the measurement site, the thickness of the coating layer 2 refers to the average value when measuring multiple sites. In addition, the average thickness of the coating layer can also be greater than 1 nm and less than 15 nm.
[0088] (Configuration of coating layer)
[0089] In addition, the coating layer 2 is preferably present adjacent to the surface of the lithium nickel composite oxide particle 1. Whether the coating layer 2 is present adjacent to the surface of the particle 1 can be determined by whether the compound containing the constituent elements of the coating layer 2 is free from the surface of the lithium nickel composite oxide particle 1. When the coating layer 2 is free from the surface of the lithium nickel composite oxide particle 1, it does not contribute to the battery capacity electrochemically, and thus becomes a major factor in reducing the battery capacity per unit weight.
[0090] It should be noted that the coating layer 2 and the surface of the lithium nickel composite oxide particle 1 may not have a clear boundary line. For example, when the lithium nickel composite oxide particle 1 before coating does not contain the constituent elements of the coating layer 2 (excluding Li and O), the coating layer 2 refers to the region where the constituent elements of the coating layer 2 (excluding Li and O) are detected, and may also include the region where both the constituent elements of the coating layer 2 (excluding Li and O) and the elements constituting the lithium nickel composite oxide particle 1 are detected. In addition, when the lithium nickel composite oxide particle 1 before coating contains the constituent elements of the coating layer 2 (excluding Li and O), it refers to the region on the surface side of the particle constituting the positive electrode active material 10, and the concentration of the constituent elements of the coating layer 2 (excluding Li and O) is higher than the central part of the lithium nickel composite oxide particle 1.
[0091] In addition, the constituent elements of the coating layer 2 (excluding Li and O) may also be partially dissolved from the surface of the lithium nickel composite oxide particles into the interior. For example, a heat treatment step (S40) is performed after the coating step (S30), and depending on the conditions at this time, the constituent elements of the coating layer can be diffused into the lithium nickel composite oxide.
[0092] For example, when Ti and / or Nb are contained in the coating layer 2, Ti and / or Nb can be dissolved from the surface into the interior of the lithium nickel composite oxide particle 1. It should be noted that in the positive electrode active material 10, in order to fully exert the effect of improving the cycle characteristics, it is preferable to adjust the degree of solid solution.
[0093] 2. Method for producing positive electrode active material for lithium ion secondary battery
[0094] Next, a method for producing a positive electrode active material for a lithium ion secondary battery (hereinafter also referred to as “positive electrode active material”) according to the present embodiment will be described. By using the production method according to the present embodiment, the positive electrode active material 10 described above can be produced with high productivity.
[0095] Figure 2 , Figure 3 1 is a diagram showing an example of a method for producing a positive electrode active material according to this embodiment. Figure 2 As shown, the method for manufacturing the positive electrode active material of this embodiment comprises: a mixing step (S10) of mixing a nickel composite compound, a niobium compound and a lithium compound to obtain a mixture; a calcining step (S20) of calcining the mixture to obtain particles of a lithium nickel composite oxide; and a coating step (S30) of allowing a coating liquid to adhere to the surface of the particles of the lithium nickel composite oxide to form a coating layer. Furthermore, after the coating step (S30), a heat treatment step (S40) of heat-treating the particles of the lithium nickel composite oxide with the coating layer formed on the surface at 300°C or above may be provided.
[0096] In addition, the nickel composite compound may be a nickel composite oxide obtained by oxidatively calcining a nickel composite hydroxide adjusted by a crystallization reaction. Figure 3 As shown, the nickel composite compound can be produced by a method including a crystallization step (S1) and an oxidation roasting step (S2). Each step is described in detail below. It should be noted that the following description is an example of the production method and does not limit the production method.
[0097] (Crystallization step: S1)
[0098] In the crystallization step (S1), a nickel composite hydroxide serving as a precursor of a lithium nickel composite oxide is prepared by a crystallization reaction.
[0099] For example, a raw aqueous solution is prepared using water-soluble compounds (metal compounds) of various elements so that the mass ratio of each element is equal to the mass ratio of each element contained in the target lithium nickel composite oxide particles. The prepared raw aqueous solution is supplied to a reaction tank together with an alkali metal aqueous solution and an ammonium ion donor to carry out a neutralization crystallization reaction to obtain a nickel composite hydroxide.
[0100] The raw materials of each element can be dissolved in water at the same time to make a mixed aqueous solution, so as to manufacture a raw material aqueous solution. In addition, the raw materials of each element can also be adjusted to separate aqueous solutions, so as to make separate raw material aqueous solutions. It should be noted that when there is an undesirable situation when the raw material aqueous solution is made into a mixed aqueous solution, it is preferably adjusted to separate raw material aqueous solutions for each raw material. For example, when the liquid property of the aqueous solution of each raw material is divided into acidic and alkaline, it is preferably adjusted to separate raw material aqueous solutions for each raw material.
[0101] The metal compound used as the raw material of each element can be water-soluble as long as it can be sulfate, chloride, nitrate, etc., and from the viewpoint of cost, preferably cheap sulfate. It should be noted that, when no water-soluble suitable metal compound is found in element M, it is not necessary to add to the mixed aqueous solution of the raw material, but to add in the oxidation roasting step (S2) and the mixing step (S10) described later.
[0102] The alkali metal aqueous solution is not particularly limited, and one or more selected from the group consisting of sodium hydroxide, sodium carbonate, sodium hydrogen carbonate, potassium hydroxide, and potassium carbonate can be preferably used.
[0103] The ammonium ion donor is not particularly limited, and one or more selected from aqueous ammonia, aqueous ammonium carbonate solution, aqueous ammonium chloride solution, and aqueous ammonium sulfate solution can be preferably used.
[0104] The shape of the reaction tank is not particularly limited, and preferably a stirrer and a temperature regulator are provided in a cylindrical container with a baffle plate inside. The stirrer preferably has a motor, a shaft, and a stirring blade. The temperature regulator is preferably in a form that heats or cools the cylindrical container by circulating a heat medium outside the cylindrical container.
[0105] In the neutralization crystallization reaction of the raw material aqueous solution, the alkali metal aqueous solution, and the ammonium ion donor in the reaction tank, it is preferred to maintain the pH and the ammonia concentration at constant values.
[0106] The pH of the aqueous solution in the reaction tank is preferably adjusted to 11.0 or more and 12.2 or less based on a liquid temperature of 25°C. For example, when preparing a nickel composite hydroxide, impurities derived from anions of the metal compounds contained in the raw aqueous solution used may sometimes be mixed into the nickel composite hydroxide. However, by making the pH value of the initial aqueous solution (in the reaction tank) be 11.0 or more, it is possible to suppress the mixing of impurities derived from anions. In addition, by setting the pH of the initial aqueous solution to less than 12.2, the obtained nickel composite hydroxide can be suppressed from being micronized, and a composite hydroxide with a particle size suitable for charge and discharge reactions can be obtained.
[0107] In addition, the pH of the initial aqueous solution prepared in the reaction tank may be set to 12.0 or more and 14.0 or less based on a liquid temperature of 25°C before the crystallization reaction, and after the nucleation step, the crystallization reaction (particle growth step) may be performed at a pH lower than that of the previous step. In addition, after all the raw aqueous solution is dripped, the pH of the reaction aqueous solution may be set to 12.0 or more and 14.0 or less based on a liquid temperature of 25°C, and then the crystallization reaction may be terminated.
[0108] The ammonia concentration of the aqueous solution in the reaction tank is preferably adjusted to more than 5g / L and less than 20g / L. When the ammonia concentration is set to more than 5g / L, the Ni in the raw aqueous solution (mixed aqueous solution) becomes an ammonium complex, and the speed of precipitation from the liquid phase to the solid phase as a hydroxide is reduced, so the sphericity of the particles of the nickel composite hydroxide obtained is improved. On the other hand, when the ammonia concentration is set to less than 20g / L, the solubility of the nickel forming the ammonium complex can be suppressed to rise excessively, and the amount ratio of the nickel composite hydroxide obtained can be made to be the target amount ratio more reliably. In addition, the excessive consumption of ammonia can be suppressed, and it is preferred industrially.
[0109] The atmosphere in the reaction tank is preferably a non-oxidizing atmosphere, for example, an atmosphere having an oxygen concentration of 1% by volume or less. When the atmosphere in the reaction tank is set to a non-oxidizing atmosphere, oxidation of the raw material compounds etc. can be suppressed. For example, precipitation of oxidized cobalt and manganese as microparticles can be prevented.
[0110] The temperature in the reaction tank in the crystallization step (S1) is preferably maintained at 40°C or higher and 60°C or lower, more preferably at 45°C or higher, and further preferably at 55°C or lower.
[0111] The temperature of the reaction tank rises due to the heat of reaction and the Joule heat of stirring, so by setting the temperature in the reaction tank to 40° C. or higher, no extra energy is consumed during cooling. In addition, by setting the temperature in the reaction tank to 60° C. or lower, evaporation of ammonia from the initial aqueous solution and the reaction aqueous solution can be suppressed, making it easy to maintain the target ammonia concentration.
[0112] The particles (powder) of the lithium nickel composite oxide preferably have a narrow particle size distribution and a uniform particle size. In order to prepare such particles, it is necessary to obtain particles with a uniform particle size in the nickel composite hydroxide as its precursor. As a method for obtaining such particles, patent document 3 and the like can be specifically exemplified.
[0113] (Oxidation roasting process: S2)
[0114] After the precursor crystallization step (S1), an oxidative roasting step (S2) may be performed. In the oxidative roasting step (S2), the nickel composite hydroxide obtained in the precursor crystallization step (S1) is oxidatively roasted to obtain a nickel composite oxide. In the oxidative roasting step (S2), a heat treatment is performed in an oxygen-containing atmosphere and then cooled to room temperature, thereby obtaining a nickel composite oxide.
[0115] The calcination conditions in the oxidation calcination step (S2) are not particularly limited. For example, it is preferred to calcine in an oxygen-containing atmosphere or an air atmosphere at a temperature of 500° C. or more and 700° C. or less for 1 hour or more and 12 hours or less. When the calcination temperature is set to 500° C. or more, the nickel composite hydroxide can be completely converted into a nickel composite oxide. In addition, by making the calcination temperature be below 700° C., the specific surface area of the nickel composite oxide can be suppressed from being excessively reduced, so it is preferred.
[0116] By making the roasting time be more than 1 hour, the temperature in the calcining container can be made uniform, and the reaction can be carried out uniformly, so it is preferred. In addition, even if the roasting is carried out for a long time than 12 hours, the obtained nickel composite oxide can not observe a large change, so from the viewpoint of energy efficiency, the roasting time is preferably set to below 12 hours.
[0117] The oxygen concentration in the oxygen-containing atmosphere during calcination is preferably equal to or higher than the oxygen concentration of air, that is, 20% by volume or higher. Since an oxygen atmosphere is also possible, the upper limit of the oxygen concentration of the oxygen-containing atmosphere can be 100% by volume.
[0118] It should be noted that, for example, when the compound containing element M cannot be coprecipitated in the crystallization step (S1), for example, the nickel composite hydroxide provided in the oxidation roasting step S2 can be added with the compound containing element M in a manner having the same mass ratio as the target substance and calcined. There is no particular limitation on the compound containing element M to be added, and for example, oxides, hydroxides, carbonates or mixtures thereof can be used.
[0119] In addition, after the oxidation roasting step (S2) is completed, in the case where light sintering is observed in the obtained nickel composite oxide, a crushing treatment may also be applied. It should be noted that in the oxidation roasting step (S2), at least a portion of the nickel composite hydroxide may be converted into the nickel composite oxide, and the entire nickel composite hydroxide may not be converted into the oxide.
[0120] (Mixing process: S10)
[0121] The mixing step ( S10 ) is a step of mixing a nickel composite compound, a niobium compound, and a lithium compound to obtain a lithium mixture.
[0122] The nickel composite compound is preferably at least one of a nickel composite hydroxide and a nickel composite oxide, and more preferably a nickel composite oxide. In addition, the nickel composite compound is preferably obtained by a method including the above-mentioned crystallization step (S1) and / or the oxidizing roasting step (S2).
[0123] As the niobium compound, for example, niobic acid, niobium oxide, niobium nitrate, niobium pentachloride, etc. can be used. Among them, niobium hydroxide or niobium oxide is preferred from the viewpoint of easy availability and avoiding impurities from being mixed into the fired lithium nickel composite oxide. The niobium compound is preferably added in a solid phase. Compared with the method of coprecipitating or coating niobium in the conventionally known crystallization step, the solid phase addition of niobium does not require a chemical solution, etc., and is therefore an addition method with low environmental load and excellent productivity.
[0124] In the case of adding niobium in the solid phase, the reactivity sometimes changes depending on the particle size of the added niobium compound. In the cumulative volume distribution curve of the particle size distribution of the niobium compound, the particle size (D90) corresponding to the cumulative volume rate of 90% is preferably 0.1 μm or more and 20 μm or less, more preferably 0.1 μm or more and 10 μm or less, and further preferably 0.1 μm or more and 5 μm or less. In the case where the D90 of the niobium compound is less than 0.1 μm, there is a problem that the handling of the powder becomes very difficult. In the case where the D90 of the niobium compound is greater than 20 μm, the reactivity during sintering is reduced, the diffusion of niobium into the particles of the lithium nickel composite oxide is insufficient, and sometimes thermal stability cannot be ensured. In addition, in the case where the D90 of niobium is too large, the formation of the coating layer 2 may become uneven. It should be noted that the particle size of the niobium compound can be appropriately adjusted within the above-mentioned particle size range to obtain a positive electrode active material with desired characteristics.
[0125] The D90 of the niobium compound can be adjusted to the above range by crushing the raw material niobium compound using a pulverizer such as a ball mill, a planetary ball mill, a jet mill, a bead mill, a pin mill, etc. In addition, classification can also be performed using a dry classifier or a sieving machine as needed. It should be noted that the D90 of the niobium compound can be measured by a laser scattering diffraction method.
[0126] The niobium compound is mixed in an amount having a target niobium content relative to the total number of atoms of Ni, Mn and element M contained in the nickel composite compound. The niobium content does not change before and after the calcination step, so the niobium compound is added in an amount corresponding to the niobium addition amount of the positive electrode active material.
[0127] The lithium compound is not particularly limited, and for example, lithium hydroxide, lithium nitrate, lithium carbonate, or a mixture thereof can be used. As the lithium compound, lithium hydroxide is preferably used from the viewpoint of low melting point and high reactivity.
[0128] The lithium compound may be mixed in an amount such that the lithium content is 95 atomic % to 110 atomic % or 97 atomic % to 108 atomic % based on the total of Ni, Mn, element M and Nb (Me).
[0129] (Firing process: S20)
[0130] The calcining step (S20) is a step of calcining the obtained lithium mixture to obtain particles 1 of lithium nickel composite oxide. The calcining conditions are not particularly limited, for example, it is preferably calcined at a temperature of 700°C to 1000°C in an oxygen-containing atmosphere for 1 hour to 24 hours. In addition, it is also possible to cool to room temperature after calcining to obtain particles 1 of lithium nickel composite oxide. It should be noted that the calcining conditions such as calcining temperature, calcining time, calcining atmosphere, etc. can be appropriately adjusted within the above range to obtain the desired properties (Li site occupancy, crystallite diameter, amount of dissolved lithium ions, etc.).
[0131] When the calcination temperature is set to 700° C. or higher, the crystal structure of the lithium nickel composite oxide particle 1 can be sufficiently grown. When the calcination temperature is set to 1000° C. or lower, it is possible to suppress excessive mixing of Ni atoms into the Li site in the obtained lithium nickel composite oxide particle 1. In addition, the calcination temperature may be 750° C. or higher, 800° C. or higher, or 820° C. or higher.
[0132] By making the calcination time be more than 1 hour, the temperature in the calcination container can be made uniform, and the reaction can be carried out uniformly, so it is preferred. In addition, even if the calcination is carried out for a longer time than 24 hours, no significant change is observed in the obtained lithium nickel composite oxide, so from the viewpoint of energy efficiency, the calcination time is preferably set to less than 24 hours, can be less than 12 hours, can be less than 10 hours, and can also be less than 6 hours.
[0133] In addition, as an oxygen-containing atmosphere, an atmosphere containing 80% by volume or more of oxygen is preferred. This is because by setting the oxygen concentration in the atmosphere to 80% by volume or more, the crystal structure of the lithium nickel composite oxide particle 1 can be fully grown, so it is preferred. Since it can also be set as an oxygen atmosphere, the upper limit of the oxygen concentration of the oxygen-containing atmosphere can be set to 100% by volume.
[0134] It should be noted that, after the calcining step ( S20 ), when slight sintering is observed in the obtained lithium nickel composite oxide particles 1 , a crushing treatment may be applied.
[0135] (Coating process: S30)
[0136] The coating step ( S30 ) is a step of causing a coating liquid to adhere to the surface of the obtained lithium nickel composite oxide particle 1 to form a coating layer 2 .
[0137] The coating layer 2 is formed by, for example, mixing the lithium nickel composite oxide particles 1 with a coating liquid and drying them to form the coating layer 2 on the surface of the lithium nickel composite oxide particles 1. In addition, as described later, after coating, a heat treatment step (S40) may be optionally performed in an oxygen-containing atmosphere. An example of the coating step (S30) is described below.
[0138] First, a coating liquid is prepared in a predetermined amount (coating agent preparation step). The coating agent may be selected based on the specific surface area (m2) per unit of the lithium nickel composite oxide particles 1 obtained in the calcining step (S20). 2 / g) of the coating layer 2 (excluding Li and O).
[0139] The coating liquid contains at least one element selected from the group consisting of Al, Si, Ti, V, Ga, Ge, Zr, Nb, Mo, Ta and W. For example, the coating liquid can be prepared by dissolving a raw material compound containing constituent elements (excluding Li and O) of the target coating layer 2 in a solvent.
[0140] Examples of the raw material compound include one or more selected from the group consisting of alkoxides and chelates using a complex having a carbonyl group, a peroxide group, and the like.
[0141] From the perspective of uniform coating, the coating liquid only needs to be liquid when it adheres to the surface of the lithium nickel composite oxide particle 1. For example, it can be prepared by dissolving a compound containing the constituent elements of the coating layer 2 in a solvent so that it is liquid at room temperature, or it can be a low-melting-point compound containing the constituent elements of the coating layer 2, which is melted by low-temperature heat treatment.
[0142] It should be noted that the coating liquid may contain Li or may not contain Li. When the coating liquid does not contain Li, in the coating step (S30) and / or the heat treatment step (S40), the Li present in the particles 1 of the lithium nickel composite oxide reacts with the compound containing the above-mentioned constituent elements in the coating liquid to form the coating layer 2.
[0143] Next, the coating liquid is attached to the surface of the lithium nickel composite oxide particle 1. The coating liquid can be attached, for example, by mixing the lithium nickel composite oxide particle 1 with the coating liquid (mixture preparation step). A common mixer can be used for mixing. In addition, drying can be performed after mixing (drying step).
[0144] In addition, from the viewpoint of forming a more uniform coating layer 2 having a specific thickness, it is preferred to perform the mixture preparation step and the drying step in parallel, and preferably use a rolling flow coating device.
[0145] Since the coating liquid shrinks due to drying, when only one mixture preparation step and one drying step are performed, gaps may be formed in the formed coating layer 2. However, when a rolling flow coating device is used, since the coating liquid is sprayed onto the lithium nickel composite oxide particles 1 flowing by the airflow heated in the device, the mixture preparation step and the drying step are repeated in parallel, and a uniform coating layer without gaps can be obtained, which is preferred.
[0146] In the drying step, it is preferred to dry at a temperature that allows the solvent of the coating agent to be sufficiently removed. For example, when a rolling flow coating device is used, the air supply temperature may be set to 80° C. or higher and lower than 300° C. In addition, after the coating treatment, additional drying may be performed using a fixed type dryer.
[0147] The atmosphere in the drying step is not particularly limited, but is preferably an inert atmosphere such as air, nitrogen, or argon supplied from a compressor equipped with a dryer in order to prevent the lithium nickel composite oxide particles 1 from reacting with moisture in the atmosphere.
[0148] (Heat treatment process: S40)
[0149] Furthermore, if necessary, after the coating step (S30), a heat treatment step (S40) may be provided for heat-treating the lithium nickel composite oxide particles 1 having the coating layer 2 formed on the surface at 300° C. or higher. The heat treatment step (S40) can make the coating layer 2 and the lithium nickel composite oxide particles 1 more firmly bonded.
[0150] The heat treatment conditions in the heat treatment step ( S40 ) are not particularly limited, but heat treatment is preferably performed in an oxygen-containing atmosphere at a temperature of 300° C. to 600° C. for 1 hour to 5 hours. The oxygen-containing atmosphere may be, for example, an air atmosphere.
[0151] The oxygen concentration in the oxygen-containing atmosphere of the heat treatment step (S40) is preferably greater than the oxygen concentration of the air atmosphere, that is, the oxygen concentration is greater than 20% by volume. By making the oxygen-containing atmosphere during the heat treatment greater than the oxygen concentration of the air atmosphere, the generation of oxygen defects inside the obtained positive electrode active material 10 can be further suppressed. The oxygen-containing atmosphere may also be an oxygen atmosphere, and the upper limit of the oxygen concentration of the oxygen-containing atmosphere is 100% by volume.
[0152] When the heat treatment temperature is 300°C or higher, impurities contained in the coating solution can be further suppressed from remaining inside the positive electrode active material 10. When the heat treatment temperature is 600°C or lower, excessive diffusion of components of the coating layer 2 can be suppressed, and the morphology of the coating layer 2 can be maintained.
[0153] When the heat treatment time is 1 hour or longer, it is possible to further suppress the impurities contained in the coating solution from remaining inside the positive electrode active material 10. In addition, even when the heat treatment time is longer than 5 hours, no significant changes are observed in the obtained positive electrode active material 10. Therefore, from the viewpoint of energy efficiency, the heat treatment time is preferably 5 hours or less.
[0154] After the heat treatment step ( S40 ), the mixture is cooled to room temperature, and a positive electrode active material having lithium nickel composite oxide particles 1 and a coating layer 2 on the surface thereof can be obtained as a final product.
[0155] It should be noted that the heat treatment step (S40) may not be performed. That is, the coating step (S30) may be performed to manufacture the positive electrode active material 10. This is because, even without the heat treatment step (S40), a coating layer can be uniformly and firmly formed on the surface of the particles of the lithium nickel composite oxide. Even without the heat treatment step, it is preferred to dry as needed to reduce and remove the solvent, water, etc. of the coating agent.
[0156] When slight sintering is observed in the positive electrode active material 10 obtained after the coating step ( S30 ) and / or the heat treatment step ( S40 ), a crushing treatment may be further performed.
[0157] 3. Lithium-ion secondary battery
[0158] The lithium-ion secondary battery (hereinafter also referred to as "secondary battery") of the present embodiment includes, for example, a positive electrode, a negative electrode and an electrolyte, and the positive electrode includes the above-mentioned positive electrode active material. The lithium-ion secondary battery formed by making a positive electrode using the above-mentioned positive electrode active material and assembling the positive electrode has excellent charge and discharge cycle characteristics. In addition, the lithium-ion secondary battery particularly preferably uses particles of the lithium nickel composite oxide obtained by the above-mentioned manufacturing method as the positive electrode active material.
[0159] The secondary battery, for example, has a positive electrode, a negative electrode, and a non-aqueous electrolyte. In addition, the secondary battery can be any secondary battery that is charged and discharged by the separation and insertion of lithium ions, for example, it can be a non-aqueous electrolyte secondary battery. It should be noted that the embodiments described below are merely illustrative, and the secondary battery of this embodiment can also be applied to various modified and improved embodiments based on the embodiments described in this specification.
[0160] (1) Components
[0161] a) Positive electrode
[0162] Using the above-mentioned positive electrode active material, a positive electrode of a lithium ion secondary battery is produced, for example, as follows.
[0163] First, a conductive material and a binder are mixed in the positive electrode active material of the present invention, and activated carbon, a solvent for viscosity adjustment, etc. are further added as needed, and they are kneaded to make a positive electrode mixture paste. At this time, each mixing ratio in the positive electrode mixture paste also becomes an important factor in determining the performance of the lithium ion secondary battery. For example, when the solid content of the positive electrode mixture other than the solvent is set to 100 parts by mass, the content of the positive electrode active material can be set to 60 parts by mass to 95 parts by mass, the content of the conductive material can be set to 1 part by mass to 20 parts by mass, and the content of the binder can be set to 1 part by mass to 20 parts by mass, as with the positive electrode of a conventional lithium ion secondary battery.
[0164] The obtained positive electrode mixture paste is applied on the surface of a collector made of, for example, aluminum foil, and dried to disperse the solvent. As required, in order to increase the electrode density, pressure is sometimes applied by rolling, etc. In this way, a sheet-like positive electrode can be made. The sheet-like positive electrode can be made into an appropriate size according to the target battery by cutting, etc., and is provided for the production of the battery. It should be noted that the production method of the positive electrode is not limited to the above-mentioned exemplified method, and other methods can also be used.
[0165] As the conductive material, for example, carbon black materials such as graphite (natural graphite, artificial graphite, expanded graphite, etc.), acetylene black, and Ketjen black can be used.
[0166] The binder plays a role of connecting and fixing the active material particles, and for example, polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), fluororubber, ethylene propylene diene rubber, styrene butadiene, cellulose resin, or polyacrylic acid can be used.
[0167] In addition, as needed, the positive electrode active material, the conductive material and the activated carbon can be dispersed, and a solvent for dissolving the binder can be added to the positive electrode mixture. As the solvent, specifically, an organic solvent such as N-methyl-2-pyrrolidone can be used. In addition, in the positive electrode mixture, activated carbon can also be added to increase the double layer capacity.
[0168] b) Negative electrode
[0169] The negative electrode can use metallic lithium, lithium alloy, etc. In addition, the following material can be used, namely: a binder is mixed in a negative electrode active material capable of absorbing and detaching lithium ions, a suitable solvent is added to make a paste, the negative electrode mixture thus obtained is applied on the surface of a metal foil collector such as copper and dried, and compressed as needed to increase the electrode density, thereby forming a material.
[0170] As the negative electrode active material, for example, lithium-containing materials such as metallic lithium and lithium alloys, natural graphite, artificial graphite, sintered organic compounds such as phenolic resins, and powders of carbon materials such as coke that can absorb and release lithium ions can be used. In this case, as the negative electrode binder, fluorine-containing resins such as PVDF can be used, as the solvent for dispersing these active materials and binders, organic solvents such as N-methyl-2-pyrrolidone can be used.
[0171] c) Diaphragm
[0172] The separator is sandwiched between the positive electrode and the negative electrode and has the function of separating the positive electrode from the negative electrode and retaining the electrolyte. As such a separator, for example, a thin film having a plurality of micropores such as polyethylene or polypropylene can be used, and there is no particular limitation as long as it has the above-mentioned function.
[0173] d) Non-aqueous electrolyte
[0174] The non-aqueous electrolyte is prepared by dissolving a lithium salt as a supporting salt in an organic solvent.
[0175] As the organic solvent, one selected from cyclic carbonates such as ethylene carbonate, propylene carbonate, butylene carbonate and trifluoropropylene carbonate, chain carbonates such as diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate and dipropyl carbonate, ether compounds such as tetrahydrofuran, 2-methyltetrahydrofuran and dimethoxyethane, sulfur compounds such as ethyl methyl sulfone and butane sultone, phosphorus compounds such as triethyl phosphate and trioctyl phosphate, etc. can be used alone, or two or more thereof can be used in combination.
[0176] As supporting salts, LiPF6, LiBF4, LiClO4, LiAsF6, LiN(CF3SO2)2, and complex salts thereof can be used.
[0177] It should be noted that the non-aqueous electrolyte may contain a radical scavenger, a surfactant, a flame retardant, and the like.
[0178] (2) Lithium-ion secondary battery
[0179] The lithium-ion secondary battery composed of the above positive electrode, negative electrode, separator and non-aqueous electrolyte can be made into various shapes such as cylindrical and stacked. In the case of any shape, the positive electrode and the negative electrode are stacked through the separator to form an electrode body, the non-aqueous electrolyte is impregnated in the obtained electrode body, and the positive electrode collector is connected to the positive terminal leading to the outside and the negative electrode collector is connected to the negative terminal leading to the outside using a collector lead, and the battery is sealed in a battery case to complete the lithium-ion secondary battery.
[0180] (3) Characteristics of lithium-ion secondary batteries
[0181] The lithium-ion secondary battery of this embodiment has a high cycle capacity retention rate (durability), and can be used appropriately when charging and discharging at a high voltage (for example, an upper limit voltage of 4.5 V or more based on metal lithium). Figure 5 The laminated battery shown in the figure was conditioned and the current density was set to 2.7 mA / cm in a thermostatic chamber maintained at 60°C. 2 , charged to a cut-off voltage of 4.5V, paused for 1 hour, and then discharged to a cut-off voltage of 3.0V. When such a cycle is repeated for 200 cycles, the cycle capacity retention rate (discharge capacity after 200 cycles / initial discharge capacity (%)) is preferably above 80%, and more preferably above 90%.
[0182] It should be noted that the so-called conditioning means that the current density is set to 0.33 mA / cm in a constant temperature chamber maintained at 25°C. 2 , charged to a cut-off voltage of 4.5 V, and after pausing for 1 hour, discharged to a cut-off voltage of 3.0 V, and the above cycle was repeated 5 times. In addition, the discharge capacity obtained in the first cycle after adjustment can be set as the initial discharge capacity, and the ratio of the discharge capacity obtained in the 200th cycle after adjustment divided by the initial discharge capacity can be used as the capacity retention rate.
[0183] In the laminated battery used for evaluation of the cycle capacity retention rate, for example, a sheet formed by applying a negative electrode mixture paste obtained by mixing graphite powder and polyvinylidene fluoride on a copper foil is used as the negative electrode.
[0184] Furthermore, since the above-described positive electrode active material is used as the positive electrode material, the lithium ion secondary battery of the present embodiment is excellent in capacity characteristics and also excellent in output characteristics.
[0185] For example, the positive electrode active material of this embodiment is used for the positive electrode to form the following Figure 4 In the case of the 2032-type coin cell (for evaluation) shown in FIG. 1 , the initial discharge capacity can be preferably 180 mAh / g or more, more preferably 185 mAh / g or more, and more preferably 195 mAh / g or more. In addition, it should be noted that the initial discharge capacity is obtained by setting the current density to 0.1 mA / cm 2 , charge to a cut-off voltage of 4.5V, pause for 1 hour, and discharge to the discharge capacity when the cut-off voltage is 3.0V.
[0186] (4) Application
[0187] As described above, the lithium ion secondary battery of the present invention has excellent capacity characteristics, output characteristics and cycle characteristics, and can be suitably used as a power source for small portable electronic devices (notebook personal computers, mobile phone terminals, etc.) that require these characteristics at a high level. In addition, the lithium ion secondary battery of the present invention is not only excellent in safety, but also can be miniaturized and high-output, and can also simplify expensive protection circuits, so it can also be suitably used as a power source for transportation equipment with limited space.
[0188] Example
[0189] Hereinafter, the present invention will be specifically described using Examples and Comparative Examples.
[0190] [Example 1]
[0191] 1. Production of lithium nickel composite oxide
[0192] The lithium nickel composite oxide is produced through the following steps.
[0193] (a) Crystallization process
[0194] 10 L of pure water was added to a reaction tank having an internal volume of 60 L, and the temperature in the tank was maintained at 50° C. with stirring. At this time, the reaction tank was set to a nitrogen atmosphere with an oxygen concentration of 1% by volume or less.
[0195] Appropriate amounts of 25 mass % sodium hydroxide aqueous solution and 25 mass % ammonia water were added to the reaction tank to prepare an initial aqueous solution so that the pH value at a liquid temperature of 25° C. was 12.8 and the ammonia concentration of the solution in the reaction tank was 15 g / L.
[0196] At the same time, nickel sulfate, cobalt sulfate and manganese sulfate were dissolved in pure water so that the mass ratio of nickel, cobalt and manganese was Ni:Co:Mn=0.78:0.11:0.11 to prepare 25 L of a 2.0 mol / L nickel-cobalt-manganese mixed aqueous solution. In addition, 5 L of a 0.37 mol / L aluminum sulfate aqueous solution was prepared.
[0197] To the initial aqueous solution in the reaction tank, 66 mL of a mixed aqueous solution of nickel, cobalt and manganese was added dropwise at 109 mL / min to prepare a reaction aqueous solution. At this time, 25% by mass ammonia water and 25% by mass sodium hydroxide aqueous solution were also added dropwise to the initial aqueous solution at a certain rate, and the pH value of the reaction aqueous solution was controlled to be maintained at 12.8 based on a liquid temperature of 25°C.
[0198] Next, sulfuric acid was added dropwise to the reaction tank to adjust the pH of the reaction aqueous solution to 11.5. This operation is intended to reduce the pH, thereby reducing the rate at which the composite hydroxide of Ni, Co, Mn and Al precipitates from the liquid phase to the solid phase in the subsequent crystallization step (particle growth step), thereby improving the uniformity of the obtained particle size distribution and the sphericity of the particles.
[0199] After controlling the pH, 26.2 L of a mixed aqueous solution of nickel, cobalt and manganese was added to the reaction solution in the reaction tank at 109.2 mL / min, and 5.9 L of an aqueous solution of aluminum sulfate was added at 24.8 mL / min. At this time, 25% by mass ammonia water and 25% by mass sodium hydroxide aqueous solution were also added to the initial aqueous solution at a certain rate, and the pH value of the reaction aqueous solution was maintained at 11.5 based on a liquid temperature of 25° C., and the ammonia concentration was maintained at 15 g / L.
[0200] After all the nickel-cobalt-manganese mixed aqueous solution and aluminum sulfate aqueous solution were dropped, the pH of the reaction aqueous solution in the reaction tank was raised until the pH reached 13.0 based on a liquid temperature of 25° C. This operation is intended to precipitate nickel ions dissolved in the liquid phase by ammine complexation on the hydroxide to obtain the target chemical composition.
[0201] Then, the reaction aqueous solution was subjected to solid-liquid separation using a Buchner funnel, a filter tank and a vacuum pump vacuum filter. Furthermore, the obtained solid phase was dispersed in 20 L of pure water at 40° C. for solid-liquid separation, and this operation was repeated twice to remove water-soluble impurities such as sodium sulfate from the nickel composite hydroxide.
[0202] The cake-like solid phase after solid-liquid separation after washing was dried in a fixed type dryer at 120° C. in an air atmosphere for 24 hours and then passed through a sieve with a mesh size of 100 μm to obtain a powdery nickel composite hydroxide.
[0203] (b) Oxidation roasting process
[0204] The prepared composite hydroxide was calcined at 600° C. for 2 hours in an air atmosphere having an oxygen concentration of 20 vol % using an atmosphere calcining furnace (BM-50100M manufactured by SILICONIT CORPORATION) and then cooled to room temperature to obtain a nickel composite oxide.
[0205] (c) Mixing process
[0206] In the nickel composite oxide, niobate (Nb2O3·xH2O) powder manufactured by Mitsuwa Chemicals Co., Ltd. is added in a manner such that the amount of Nb becomes 0.1% with respect to the total amount of Ni, Co, Mn and Al contained in the nickel composite oxide, and lithium hydroxide monohydrate is added in a manner such that the amount of Li becomes 103% with respect to the total amount of Ni, Co, Mn, Al and Nb, and the mixture is mixed using a TURBULA-Shaker mixer (T2F, manufactured by DALTON Co., Ltd.) to obtain a lithium mixture.
[0207] (d) Firing process
[0208] The obtained lithium mixture was calcined at 875° C. for 5 hours in an oxygen-containing atmosphere having an oxygen concentration of 90% by volume or more using an atmosphere calcining furnace (BM-50100M manufactured by SILICONIT CORPORATION), and then cooled to room temperature to obtain lithium nickel composite oxide particles.
[0209] 2. Evaluation of Lithium Nickel Composite Oxide Particles
[0210] The obtained lithium nickel composite oxide was evaluated as follows.
[0211] (a) Composition
[0212] Analysis using an ICP emission spectrometer (725ES, manufactured by VARIAN) confirmed that the amount ratio of Li, Ni, Co, Mn, Al, and Nb in the lithium nickel composite oxide was Li:Ni:Co:Mn:Al:Nb=1.03:0.750:0.108:0.108:0.03:0.004.
[0213] (b) Crystal structure
[0214] The crystal structure of the lithium nickel composite oxide particles was measured using XRD (PROMRD, X'Pert, manufactured by Panalytical Corporation). It was confirmed that the crystal structure was a layered rock salt type crystal structure in which a peak attributed to the R-3m structure was detected in the diffraction pattern.
[0215] In addition, the half-value width of the peak attributed to the (003) plane in the diffraction pattern was measured and the size of the crystallite was calculated using the Scherrer method, and the result was 113 nm.
[0216] (c) Determination of the amount of dissolved lithium ions
[0217] The amount of dissolved lithium ions in the lithium nickel composite oxide was determined by titration. 2.0 g of lithium nickel composite oxide was dispersed in 125 ml of pure water, and 2 mL of 10% barium chloride solution was further added. While stirring, neutralization titration was performed with 1 mol / L hydrochloric acid, and the amount of 1 mol / L hydrochloric acid required until the inflection point near pH 4 of the obtained titration curve was converted into the amount of Li derived from dissolved lithium ions. As a result, the amount of dissolved lithium ions in the lithium nickel composite oxide was 0.47 wt%.
[0218] (d) Specific surface area
[0219] The BET specific surface area of the lithium nickel composite oxide was measured using a fully automatic BET specific surface area measuring device (Macsorb, manufactured by Mountech Co., Ltd.) and was confirmed to be 0.56 m 2 / g.
[0220] (e) Particle size distribution
[0221] The particle size distribution of the lithium nickel composite oxide was measured using a laser diffraction scattering particle size distribution measuring device (Microtrac HRA, manufactured by Nikkiso Co., Ltd.). The results showed that the volume-based average particle size D50 was 4.7 μm, and the average particle size D10, D90, and M V Calculated deviation index ((D90-D10) / M V ) is 0.43.
[0222] 3. Coating of lithium nickel composite oxide
[0223] The obtained lithium nickel composite oxide was subjected to the following coating step.
[0224] In a solution prepared by adding 30 ml of isopropyl alcohol (IPA) and 1.8 g of tetrabutoxytitanium (Ti-BuOH) and stirring, a solution prepared by adding 20 ml of IPA and 0.9 g of acetylacetone was added dropwise at 60°C while heating and stirring. This is to avoid adding high concentrations of acetylacetone directly to the Ti solution. Then, a solution prepared by adding 0.54 g of pure water to 10 ml of IPA was added to the cooled solution. Finally, 65 ml of IPA was added to the obtained solution to adjust the coating solution.
[0225] Using the coating solution, 500 g of the lithium nickel composite oxide was coated using a rolling flow coating device (MP-01, POWREX).
[0226] Using a flow rate of 0.3m / s heated to 120°C 3 500 g of lithium nickel composite oxide was flowed in the chamber by air at a flow rate of / h, and the coating liquid was sprayed on the lithium nickel composite oxide at a flow rate of 1.7 ml / min.
[0227] After the coating liquid was completely sprayed, the lithium nickel composite oxide was recovered from the chamber and heat treated at 400° C. for 5 hours under oxygen flow using an atmosphere sintering furnace (BM-50100M manufactured by SILICONIT Co., Ltd.). Then, it was cooled to room temperature to obtain lithium nickel composite oxide particles (positive electrode active material) having a coating layer (containing Li and Ti).
[0228] 4. Evaluation of Lithium Nickel Composite Oxide Particles Having a Coating Layer
[0229] (a) Composition
[0230] The analysis using an ICP emission spectrometer (Varian, 725ES) confirmed that the coated lithium nickel composite oxide contained 0.88 wt% Ti and the amount of Ti per unit area of the base material was 370 μmol / m 2 .
[0231] (b) Thickness of coating layer
[0232] The coated lithium nickel composite oxide sliced with CRYO ION SLICER (JEOL, IB-09060CIS) was observed using TEM (JEOL, JEM-ARM200F), and it was confirmed that the thickness of the coating layer was 11 nm.
[0233] [Manufacturing of coin-type batteries]
[0234] Initial discharge capacity use Figure 4 The 2032-type coin cell CBA shown in the figure was evaluated. The electrodes of the coin cell CBA are composed of a positive electrode PE, a separator SE1, and a negative electrode NE, which are stacked in order. In addition, the positive electrode PE is housed in a casing in such a way that it contacts the inner surface of the positive electrode can PC and the negative electrode NE contacts the inner surface of the negative electrode can NC.
[0235] The positive electrode PE was prepared as follows: 52.5 mg of the positive electrode active material obtained as described above, 15 mg of acetylene black and 7.5 mg of PTFE were mixed, pressed at a pressure of 100 MPa into a shape of 11 mm in diameter and 100 μm in thickness, and then dried in a vacuum dryer at 120° C. for 12 hours to obtain a positive electrode PE.
[0236] Next, using this positive electrode PE, a Figure 4 The 2032-type coin cell CBA shown.
[0237] The negative electrode NE uses lithium metal with a diameter of 17 mm and a thickness of 1 mm, and the electrolyte uses an equal amount of ethylene carbonate (EC) and diethyl carbonate (DEC) with 1M LiClO4 as the supporting electrolyte (manufactured by Toyama Pharmaceutical Industry Co., Ltd.). In addition, the separator SE1 uses a polyethylene porous membrane with a thickness of 25 μm. It should be noted that the 2032-type coin battery CBA has a gasket GA and is assembled into a coin-shaped battery by the positive electrode tank PC and the negative electrode tank NC.
[0238] [Initial discharge capacity]
[0239] After making a 2032-type coin battery CBA, place it for about 24 hours. After the open circuit voltage OCV (Open Circuit Voltage) stabilizes, perform the following charge and discharge test to find the initial discharge capacity, that is, set the current density to the positive electrode to 0.1 mA / cm 2 , charged to a cut-off voltage of 4.5V, and after pausing for 1 hour, discharged to a cut-off voltage of 3.0V, and the discharge capacity at this time was measured. As a result, it was confirmed that the initial discharge capacity was 196mAh / g. It should be noted that the initial discharge capacity was measured using a battery charge and discharge system (manufactured by Hokuto Electric Co., Ltd., HJ1001SD8).
[0240] [Fabrication of laminated batteries]
[0241] Cyclic feature usage Figure 5 The laminated battery LBA shown was evaluated.
[0242] like Figure 5 As shown, the laminated battery LBA has a structure in which the electrolyte is impregnated in the laminate of the positive electrode film PS, the separator SE2 and the negative electrode film NS by the coating LA. It should be noted that the positive electrode film PS is connected to the positive electrode side tab lead PL, and the negative electrode film NS is connected to the negative electrode side tab lead NL, and the positive electrode side tab lead PL and the negative electrode side tab lead NL are exposed outside the coating LA.
[0243] 20.0 g of the obtained positive electrode active material, 2.35 g of acetylene black and 1.18 g of polyvinylidene fluoride were dispersed in N-methyl-2-pyrrolidone (NMP), and the obtained slurry was spread at 1 cm 27.0 mg of positive electrode active material is coated on Al foil. Next, the material coated with the slurry containing the positive electrode active material on the Al foil is dried at 120°C in the atmosphere for 30 minutes to remove NMP. The Al foil coated with the positive electrode active material is cut into strips with a width of 66 mm and rolled at a load of 1.2 t to make a positive electrode film. Then, the positive electrode film is cut into a rectangle of 50 mm × 30 mm, dried at 120°C for 12 hours in a vacuum dryer, and used as the positive electrode film PS of the laminated battery LBA.
[0244] In addition, a negative electrode film NS was prepared by applying a negative electrode mixture paste of a mixture of graphite powder and polyvinylidene fluoride having an average particle size of about 20 μm on a copper foil. A polyethylene porous film having a film thickness of 20 μm was used as the separator SE2, and a 3:7 mixed solution of ethylene carbonate (EC) and diethyl carbonate (DEC) (manufactured by Ube Industries, Ltd.) with 1M LiPF6 as a supporting electrolyte was used as the electrolyte.
[0245] In a dry room whose dew point was controlled at -60°C, the stack of the positive electrode film PS, the separator SE2, and the negative electrode film NS was impregnated with an electrolyte solution and sealed with a cover film LA to produce a laminated battery LBA.
[0246] [Cycle characteristics]
[0247] The cycle characteristics were evaluated by measuring the capacity retention rate when the laminated battery LBA was charged and discharged for 200 cycles. Specifically, the laminated battery LBA was adjusted as follows: first, in a thermostatic chamber maintained at 25°C, the current density was set to 0.33 mA / cm 2 , charge to a cut-off voltage of 4.5 V, rest for 1 hour, and then discharge to a cut-off voltage of 3.0 V. Repeat the above cycle 5 times. Then, in a thermostat maintained at 60°C, set the current density to 2.7 mA / cm 2 , charged to a cut-off voltage of 4.5 V, rested for 1 hour, and then discharged to a cut-off voltage of 3.0 V. This cycle was repeated 200 times, and the discharge capacity of each cycle was measured for evaluation.
[0248] The capacity retention rate, which was a ratio obtained by dividing the discharge capacity obtained at the 200th cycle after adjustment by the discharge capacity obtained at the first cycle after adjustment, was 82%.
[0249] [Example 2]
[0250] The coated lithium nickel composite oxide was synthesized under the same conditions as in Example 1 except that the ratio of Ni:Co:Mn:Al:Nb in the lithium nickel composite oxide synthesis step of Example 1 was 0.75:0.054:0.162:0.03:0.004. The results are shown in Table 1.
[0251] [Example 3]
[0252] The coated lithium nickel composite oxide was synthesized under the same conditions as in Example 1 except that the ratio of Ni:Co:Mn:Al:Nb in the lithium nickel composite oxide synthesis step of Example 1 was 0.65:0.158:0.158:0.03:0.004. The results are shown in Table 1.
[0253] [Example 4]
[0254] The coated lithium nickel composite oxide was synthesized under the same conditions as in Example 1 except that the ratio of Ni:Co:Mn:Al:Nb in the lithium nickel composite oxide synthesis step of Example 1 was 0.65:0.079:0.238:0.03:0.004. The results are shown in Table 1.
[0255] [Example 5]
[0256] The coated lithium nickel composite oxide was synthesized under the same conditions as in Example 1 except that the ratio of Ni:Co:Mn:Al:Nb in the lithium nickel composite oxide synthesis step of Example 1 was 0.55:0.208:0.208:0.03:0.004. The results are shown in Table 1.
[0257] [Example 6]
[0258] The coated lithium nickel composite oxide was synthesized under the same conditions as in Example 1 except that the ratio of Ni:Co:Mn:Al:Nb in the lithium nickel composite oxide synthesis step of Example 1 was 0.55:0.104:0.312:0.03:0.004. The results are shown in Table 1.
[0259] [Comparative Example 1]
[0260] The coated lithium nickel composite oxide was synthesized under the same conditions as in Example 1 except that the Li / M ratio in the lithium nickel composite oxide synthesis step of Example 1 was 1.08.
[0261] [Comparative Example 2]
[0262] The coated lithium nickel composite oxide was synthesized under the same conditions as in Example 1 except that the average particle size D50 in the lithium nickel composite oxide synthesis step of Example 1 was 11.3 μm.
[0263] [Comparative Example 3]
[0264] The coated lithium nickel composite oxide was synthesized under the same conditions as in Example 2 except that the coating of the lithium nickel composite oxide particles in Example 1 was not performed.
[0265] [Table 1]
[0266]
[0267] [Evaluation results]
[0268] The positive electrode active material of the embodiment has a significantly improved cycle capacity maintenance rate in the lithium ion secondary battery compared to the positive electrode active material of Comparative Example 1 (Li site occupancy is 98% or more). In addition, the positive electrode active material of Example 1 has a further improved cycle capacity maintenance rate compared to the positive electrode active material of Reference Example 1 manufactured under the same conditions except that Nb is not added. In particular, in Examples 4 and 6 where the Li site occupancy is low, the cycle capacity maintenance rate is significantly improved.
[0269] On the other hand, in the case of the positive electrode active material of Comparative Example 2 having a large average particle diameter D50 (11.3 μm), the cycle capacity retention rate was low.
[0270] In addition, in the case of the positive electrode active material of Comparative Example 3, which was manufactured under the same conditions as Example 1 except that it did not have a coating layer, the cycle capacity retention rate of the lithium ion secondary battery was low. This is considered to be because there is no coating layer on the surface of the lithium nickel composite oxide particles, so the interface resistance between the positive electrode active material and the electrolyte increases.
[0271] According to the present invention, it is possible to provide a positive electrode active material that can be suitably used in a positive electrode of a lithium ion secondary battery that requires a high battery capacity, and a method for producing the same.
[0272] It should be noted that the technical scope of the present invention is not limited to the methods described in the above-mentioned embodiments, etc. One or more of the requirements described in the above-mentioned embodiments, etc. are sometimes omitted. In addition, the requirements described in the above-mentioned embodiments, etc. can be appropriately combined. And, as long as the law permits, the disclosure of all documents cited in Japanese Patent Application No. 2022-084104 and the above-mentioned embodiments, etc., which are Japanese patent applications, is cited as part of the disclosure of this document.
[0273] Description of Reference Numerals
[0274] 1: Lithium nickel composite oxide particles,
[0275] 2: coating layer,
[0276] CBA: Coin-type battery,
[0277] PE: positive electrode (evaluation electrode),
[0278] NE: Negative electrode,
[0279] SE1: Diaphragm,
[0280] GA: gasket,
[0281] PC: positive electrode tank,
[0282] NC: Negative tank,
[0283] LBA: Laminated Battery,
[0284] PS: positive electrode,
[0285] NS: negative electrode,
[0286] SE2: Diaphragm,
[0287] LA: Lamination,
[0288] PL: positive side ear lead,
[0289] NL: Negative side tab lead.
Claims
1. A positive electrode active material for a lithium ion secondary battery, which has particles of a lithium nickel composite oxide and a coating layer covering the surface of the particles, The lithium nickel composite oxide particles have a crystal structure belonging to the space group R-3m, and contain at least Li, Ni, Mn, element M and Nb, and the amount ratio of the elements is represented by Li:Ni:Mn:M:Nb=a:(1-xyz):x:y:z, wherein, 0.95 ≤ a ≤ 1.10, 0 < x ≤ 0.5, 0 < y ≤ 0.5, 0 < x + y + z ≤ 0.7, 0 < z < 0.05, the element M is Co, or the element M is Co and at least one selected from the group consisting of Al, Zr, Si, Zn, and Ti, The Li site occupancy is 92% or more and 98% or less, In the cumulative volume distribution curve of the particle size distribution, the particle diameter D50 corresponding to a cumulative volume rate of 50% is 8 μm or less, The crystallite diameter calculated by the Scherrer method from the diffraction peak attributed to the (003) plane measured by XRD is 70 nm or more and 140 nm or less, The amount of eluted lithium ions determined by neutralization titration is 0.20 mass% or more and 1.00 mass% or less relative to the total amount of the particles of the lithium nickel composite oxide, The coating layer is a composite oxide containing Li and at least one element selected from the group consisting of Al, Si, Ti, V, Ga, Ge, Zr, Nb, Mo, Ta, and W.
2. The positive electrode active material for lithium ion secondary battery according to claim 1, wherein The lithium nickel composite oxide particles include secondary particles formed by agglomeration of a plurality of primary particles, have a porous structure having a plurality of voids in the secondary particles where the primary particles do not exist, and have a specific surface area of 0.3 m2 as measured by a nitrogen adsorption BET method. 2 / g or more and 2.0m 2 / g or less.
3. The positive electrode active material for lithium ion secondary battery according to claim 1 or 2, wherein At least a part of the niobium contained in the particles of the lithium nickel composite oxide segregates at the interface of the primary particles.
4. The positive electrode active material for lithium ion secondary battery according to claim 1 or 2, wherein The average thickness of the coating layer is 1 nm or more and 15 nm or less.
5. A method for manufacturing a positive electrode active material for a lithium ion secondary battery according to claim 1 or 2, which comprises: A mixing step of mixing a nickel composite compound, a niobium compound, and a lithium compound to obtain a mixture; A firing step of firing the mixture to obtain the particles of the lithium nickel composite oxide; and A coating step of causing a coating liquid containing at least one element selected from the group consisting of Al, Si, Ti, V, Ga, Ge, Zr, Nb, Mo, Ta, and W to adhere to the surface of the particles of the lithium nickel composite oxide to form the coating layer.
6. The method for producing a positive electrode active material for a lithium ion secondary battery according to claim 5, wherein: The nickel composite compound contains a nickel composite oxide, The method for manufacturing a positive electrode active material for a lithium ion secondary battery comprises an oxidation roasting step of subjecting a nickel composite hydroxide adjusted by a crystallization reaction to oxidation roasting to obtain the nickel composite oxide.
7. The method for producing a positive electrode active material for a lithium ion secondary battery according to claim 5, wherein: After the coating step, there is a heat treatment step of heat-treating the particles of the lithium nickel composite oxide having the coating layer formed on the surface at 300°C or higher.
Citation Information
Patent Citations
Breeding device
JP2022084104A
Li-Ni COMPLEX OXIDE PARTICLE POWDER AND NON-AQUEOUS ELECTROLYTE SECONDARY BATTERY
WO2014061654A1